Sensory Perception Through Shape Analysis of the Florianópolis Museum - Nascimento, Vanessa Helena Pires da Costa do; Pfützenreuter, Andrea Holz (National Journal of City Management, 2023)
The Florianópolis Museum is located in the former building of the Casa de Câmara e Cadeia of the city, presenting colonial features, and later, in the early twentieth century, eclectic mentions were included. The objective of the article was to analyze the building of the Florianópolis Museum in relation to the form and the sensorial perceptions, through two on-site visits referencing the theories of Pallasma, for the analysis of sensorial perceptions; and Clark and Pause for the analysis of the form of the built environment and its influence on perceptions. For the Museum, the importance of the contrast between light and shade to highlight ornaments or to make the environment more intimate was perceived; of natural materials that allow an understanding of the finitude of life and the "passing of time"; of sounds and smells that recall a memory; of symmetry for the understanding of the space as a whole and of robustness for the propagation of sounds and the sensation of silence, as well as the importance of different textures for the composition of the building. Based on the analyses, it was found that there is a correlation between perception, form and function of the building, however, these are individual sensations and experiences. The experience of the collective influences the individuality of the being, as much as the choices of each one modify the collective scenario.